Design and baseline characteristics of the Biomarkers Of Risk In Colorectal Cancer (BORICC) Follow-Up study: A 12+ years follow-up. Issue 3 (September 2019) - Malcomson, FC; Breininger, SP; ElGendy, K; Joel, A; Ranathunga, RMTK; Hill, TR; Bradburn, D Michael; Turnbull, DM; Greaves, LC; Mathers, JC
Background: Colorectal cancer (CRC) is the third most common cancer worldwide. Age is the strongest non-modifiable risk factor but it is estimated that over half of CRC cases are linked with lifestyle factors such as diet. The Biomarkers Of RIsk of Colorectal Cancer (BORICC) Study recruited 363 participants in 2005 to investigate the effects of lifestyle factors on biomarkers of CRC risk. Aim: In the present BORICC Follow-Up (BFU) Study, we are using a longitudinal study design to investigate the effects of ageing (12+ years) and lifestyle factors on biomarkers of CRC risk and on healthy ageing. Methods: BFU Study participants attended a study visit at North Tyneside General Hospital (UK) for collection of biological samples, including blood and rectal biopsies, and information collected included anthropometric measurements, a Health & Medications Questionnaire, physical activity and sedentary behaviour, and habitual diet. Furthermore, musculoskeletal function was assessed by heel bone densitometry, timed up and go and hand grip strength as markers of healthy ageing. The BFU Study outcomes will be similar to those measured at baseline in the BORICC Study, such as DNA methylation and mitochondrial function, with additional measurements including the gut microbiome, faecal short-chain fatty acid concentrations and expression of genes associated with CRC. Results: Participants' recruitment to BFU Study and all sample and data collection have been completed. Forty-seven of the original BORICC participants were re-recruited to the BFU Study (mean age 67 years, 51% female). The recruits included 37 initially healthy participants and 10 participants who had adenomatous polyps at baseline. Approximately 70% of participants were over-weight or obese. Conclusion: Ultimately, identifying lifestyle factors that can reduce CRC risk, and understanding the underlying mechanisms for the effects of lifestyle and ageing on CRC risk, could lead to early prevention strategies.